Reply to comment by S. P. Neuman on "Advective transport in heterogeneous aquifers: Are proxy models predictive?". Issue 7 (30th July 2016) - Fiori, Aldo; Zarlenga, Antonio; Gotovac, Hrvoje; Jankovic, Igor; Volpi, Elena; Cvetkovic, Vladimir; Dagan, Gedeon
Abstract: In this Reply we further comment on the main assumptions and the results of our recent manuscript "Advective transport in heterogeneous aquifers: Are proxy models predictive?" Key Points: Markovianity and relevance of the assumptions are discussed